2011
DOI: 10.1103/physreva.84.043804
|View full text |Cite
|
Sign up to set email alerts
|

Artificial gauge field for photons in coupled cavity arrays

Abstract: We propose and characterize solid-state photonic structures where light experiences an artificial gauge field. A non-trivial phase for photons tunneling between adjacent sites of a coupled cavity array can be obtained by inserting optically active materials in the structure or by inducing a suitable coupling of the propagation and polarization degrees of freedom. We also discuss the feasibility of observing strong gauge field effects in the optical spectra of realistic systems, including the Hofstadter butterf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
239
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(243 citation statements)
references
References 49 publications
2
239
1
1
Order By: Relevance
“…In the study of strongly correlated systems and collective phenomena, light has traditionally assumed the role of a spectroscopic probe. The increasing level of control over light-matter interactions with atomic and solid-state systems [1][2][3] has brought forth a new class of quantum many body systems where light and matter play equally important roles in emergent phenomena: photon lattices [4][5][6][7][8][9][10][11][12][13][14][15]. The basic building block of such systems is the elementary Cavity QED (CQED) system formed by a two-level system (TLS) interacting with a single mode of an electromagnetic resonator.…”
mentioning
confidence: 99%
“…In the study of strongly correlated systems and collective phenomena, light has traditionally assumed the role of a spectroscopic probe. The increasing level of control over light-matter interactions with atomic and solid-state systems [1][2][3] has brought forth a new class of quantum many body systems where light and matter play equally important roles in emergent phenomena: photon lattices [4][5][6][7][8][9][10][11][12][13][14][15]. The basic building block of such systems is the elementary Cavity QED (CQED) system formed by a two-level system (TLS) interacting with a single mode of an electromagnetic resonator.…”
mentioning
confidence: 99%
“…4b. As a result, the photonic frequency spectrum in this resonator array [39,40] exhibits both Landau levels and fractal patterns known as the Hofstadter butterfly, which are the signatures of a 2D electron in a uniform magnetic field: the integer quantum Hall effect. However, without T breaking, the two copies of "spin" spaces are degenerate in frequency and couple to each other.…”
Section: Coupled Resonatorsmentioning
confidence: 99%
“…In contrast, in edge-mode guiding systems [11,12,[15][16][17][18], the intensity maximum is located at the edge. This difference is of great importance in practice.…”
Section: Introductionmentioning
confidence: 90%
“…However, recent theoretical works [11,12,18,20] have shown that an effective magnetic field for photons can exist if light would accumulate a directiondependent phase when propagating. Consequently, the discussion above for electrons applies to photons in an effective gauge field as well: a properly designed photonic gauge field should be able to shift the dispersion relation in the k space.…”
Section: B Effect Of Gauge Field On Dispersion Relationmentioning
confidence: 99%
See 1 more Smart Citation